KORELASI STATUS SOSIAL EKONOMI KELUARGA TERHADAP GAYA HIDUP REMAJA DI KOTA PEKANBARU (STUDI KASUS SISWA SMA NEGERI 12 PEKANBARU) - Marlina Manalu; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Symptoms of modernization has now spread throughout the world, Unexception Indonesian which is a developing country. Modernization is change of traditional society to modern society. Technological developments changing rapidly, resulting each individual or group faced with various challenges to be able move faster. Associated with lifestyle phenomenon which doing by teenager undetached from condition famly socio-economic. This research aims to know how characteritic family socio-economic of students Senior High School 12 Pekanbaru, how the profile lifestyle of students in Senior High School 12 Pekanbaru, and there are correlation between family socio-economic to the lifestyle students. The subyek of the this research is students of class X and class XI Senior High School 12 Pekanbaru with totaliting 30 respondents. Data colletions using questionnaries and documentation metodh. Techniques analysis of test preconditions consist of validity test and reliability test. Techniques analysis using simple linear analysis technique and analysis multiple of correlation coeficient (R). The result of this research indicate that is a significant relationship between family socio-economic status of the students lifestyle with mutiple of correlation coefcient 0,545 and Fhitung 22,416.Keywords: family socio-economic status, lifestyle